2009
DOI: 10.1590/s1516-89132009000400027
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of orsellinic acid derivatives

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…This information may further support the recent suggestion of using lichen compounds, which are chemically simple and are possibly easily synthesized in the laboratory, as herbicides (Dayan and Romagni 2001;Duke et al 2002). However, the different effects, ranging from inhibition to stimulation, that have been observed on different tested plants (Peres et al 2009) will also have to be taken into account.…”
Section: Do Mycorrhizal Fungi Mediate the Effects Of Terricolous Lichsupporting
confidence: 77%
See 3 more Smart Citations
“…This information may further support the recent suggestion of using lichen compounds, which are chemically simple and are possibly easily synthesized in the laboratory, as herbicides (Dayan and Romagni 2001;Duke et al 2002). However, the different effects, ranging from inhibition to stimulation, that have been observed on different tested plants (Peres et al 2009) will also have to be taken into account.…”
Section: Do Mycorrhizal Fungi Mediate the Effects Of Terricolous Lichsupporting
confidence: 77%
“…Water extracts of terricolous lichens, including several Cladonia species and the foliose Peltigera canina, have been shown, in vitro, to reduce the seed germination of several vascular plants, including Gymnosperms (e.g., Pinus sylvestris) and Angiosperms, trees, shrubs, forbs and grasses (Pyatt 1967;Lawrey 1984;Hobbs 1985;Sedia and Ehrenfeld 2003). Growth parameters, e.g., root elongation, are even more sensitive to allelopathic effects than seed germination (Peres et al 2009): in multi-assay laboratory experiments, the growth of forbs and grasses has been inhibited by most of the tested, purified lichen metabolites at concentrations ranging from 10 (3 to 10 (9 M, while stimulation effects have been reported for a few compounds at lower concentrations (Lawrey 1984 and references therein;Nishitoba et al 1987;Cardarelli et al 1997;Rojas et al 2000;Peres et al 2009). Some authors have suggested that the chemical structure, e.g., the number and length of alkyl groups bonded to the benzene rings and to phenolic oxygen, is important in terms of activity (Nishitoba et al 1987;Peres et al 2009).…”
Section: Allelopathic Effects Of Lichens On Land Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo as RAS (BRASIL, 2009), a exposição das cipselas de alface a um período de 8 a 16 horas de luz por dia pode ser benéfica e é recomendada a fim de fornecer condições mais propícias para o crescimento das estruturas essenciais das plântulas, facilitando a avaliação e diminuindo as possibilidades de ataque por microrganismos. Entretanto, na literatura são encontrados também trabalhos que fazem o uso de luz constante (PERES et al, 2004;PERES et al, 2009;WANDSCHEER et al, 2011).…”
Section: Teste De Luminosidadeunclassified